Design of Vaccine Candidate Based on Ebola Virus Epitop With In Silico Approach - Erwin Prasetya Toepak; Sari Namarito Simarmata; Sudarman Rahman; Stevin Carolius Angga (Jurnal Sains dan Terapan Kimia, 2022)
ABSTRACT          The World Health Organization (WHO) recorded as many as 2,299 cases of death with a case percentage of 66% during 2018 to 2020 in the Democratic Republic of the Congo due to the Ebola virus. Ebola virus is a member of the Filoviridae family. One of the viro cores consists of glycoprotein (GP). Messenger RNA (mRNA) generates long GP chains for the attachment protein (GP 1) and the fusion protein (GP 2). Epitope-based vaccines are a promising approach because epitopes represent immunogenic regions that elicit immunity specifically. Epitope prediction was performed based on the GP EBOV sequence available in the Data Bank. The designed vaccine could be one of the candidates for the Ebola virus vaccine. The design of the virus with access to NCBI AAB81004 was carried out by testing such as B cell epitope, T cell, and their antigenicity using the VaxiJen v2.0 server and IEDB. The T cell epitope prediction results showed that 20 T cell epitopes interacted with the Major Histocompatibility Complex (MHC) with the highest score of 2.8069. B cell epitope by linear BepiPred assay had 77 candidate epitope peptides from sequence 401-477. Karplus and Schulz's flexibility predictions showed a predictive value of 1.119 with a threshold of 1.008, with the analyzed area having an antigenic tendency where the threshold area was yellow. Keywords: Ebolavirus; Vaccine; Epitope B Cell; Epitope T Cell; In Silico